Treaty Series Cumulative Index No. 47 - United Nations (United Nations, 2013)
This is the forty-seventh volume of the United Nations Treaty Series Cumulative Index. This volume covers the treaties and international agreements contained in volumes 2501 to 2550 of the United Nations Treaty Series (UNTS). It consists of two main sections, each preceded by an explanatory note. In the first section, Chronological Index, treaties and international agreements are listed in the order of the dates on which they were first adopted, signed or opened for signature or accession, etc. Any subsequent agreements and/or actions relating to the original agreement are to be found under the date of the original instrument. The second section, Alphabetical Index, refers to treaties and international agreements by a party and by subject.